BASICS OF DESIGN METHODOLOGY - Nodira Izzatullayevna, Yuldashova (PT. Antis International Publisher, 2025)
Objective: To explore and define the methodology of design as a systematic and structured approach to developing high-quality systems and products. The study aims to provide insights into the principles, stages, and tools used in modern design to ensure efficiency, adaptability, and user satisfaction. Method: The research employs a conceptual framework combining the definitions of methodology and design. The study examines the logical organization, methods, and means used in the design process, including principles such as systematicity, flexibility, iterativeness, and user focus. It also analyzes key approaches (classical, flexible, modular, parallel) and highlights the role of technologies such as CAD, prototyping tools, and project management software in design activities. Results: The findings identify critical stages of the design process: goal formulation, requirements analysis, concept development, detailed design, testing and validation, and implementation and maintenance. Key principles of design methodology ensure adaptability to dynamic needs and conditions while maintaining an integrated approach. Technologies like CAD and project management systems enhance the effectiveness of design activities, making them more responsive to user demands. CBLT proved effective in improving students' ability to learn and apply new words. Novelty: This study presents an integrative view of design methodology by combining classical and modern approaches, emphasizing the interplay between human creativity and machine-assisted processes (ergaticity). It highlights iterative cycles as a foundation for refinement and improvement, thus adapting traditional principles to contemporary technological advancements.